celebration building - Lidin, Konstantin (project baikal, 2020)
There is a type of buildings closely related to celebrations. First of all, it includes theatre buildings. Alexander Anisimov’s article considers the evolution of the structure and the decoration of theatre buildings in the modern and contemporary times. Revolutions in the theatrical art resonate with wonderful breakthroughs in the architectural thought. New streams are boosted at the intersection of the European architectural thought and Chinese innovative trends. Petr Kapustin’s essay is devoted to the symbolism and meanings of a tower. A tower is considered as a linking element between the sacred and the profane, the male and female, the past and the present… The esoteric and unordinary meaning of the tower makes it related to the topic of the issue. The 2018 FIFA World Cup is already fading from our memory, despite its bright festivity. It is time for a deeper analysis of the experience brought by the Championship. The article on Volgograd Arena is devoted to the cable-stayed roof system of the Complex. The design and construction of the Complex look like a real triumph of the engineering thought and, at the same time, an excellent example of international collaboration of specialists from different countries.